Efficacy and Safety of Q10 Ubiquinol With Vitamins B and E in Neurodevelopmental Disorders: A Retrospective Chart Review - Cucinotta, Francesca; Ricciardello, Arianna; Turriziani, Laura; Mancini, Arianna; Keller, Roberto; Sacco, Roberto; Persico, Antonio M. (Frontiers in Psychiatry, 2022)
Increased oxidative stress and defective mitochondrial functioning are shared features among many brain disorders. The aim of this study was to verify retrospectively the clinical efficacy and safety of a metabolic support therapy with Q10 ubiquinol, vitamin E and complex-B vitamins in various neurodevelopmental disorders. This retrospective chart review study included 59 patients (mean age 10.1 ± 1.2 y.o., range 2.5-39 years; M:F = 2.47:1), diagnosed with Autism Spectrum Disorder (n=17), Autism Spectrum Disorder with co-morbid Intellectual Disability (n=19), Intellectual Disability or Global Developmental Delay (n=15), Attention-Deficit/Hyperactivity Disorder (n=3) and Intellectual Disability in Phelan-McDermid syndrome due to chr. 22q13.33 deletion (n=5). After a minimum of three months of therapy, a positive outcome was recorded in 45/59 (76.27%) patients, with Clinical Global Impression – Improvement scores ranging between 1 (‘very much improved’) and 3 (‘minimally improved’). The most widespread improvements were recorded in cognition (n=26, 44.1%), adaptative functioning (n=26, 44.1%) and social motivation (n=19, 32.2%). Improvement rates differed by diagnosis, being observed most consistently in Phelan-McDermid Syndrome (5/5, 100%), followed by Intellectual Disability/Global Developmental Delay (13/15, 86.7%), Autism Spectrum Disorder with co-morbid Intellectual Disability (15/19, 78.9%), Autism Spectrum Disorder (11/17, 64.7%) and ADHD (1/3, 33.3%). No significant adverse event or side effect leading to treatment discontinuation were recorded. Mild side effects were reported in 18 (30.5%) patients, with the most frequent being increased hyperactivity (9/59, 15.3%). This retrospective chart review suggests that metabolic support therapy with Q10 ubiquinol, vitamin E and complex-B vitamins is well tolerated and produces some improvement in the majority of patients with neurodevelopmental disorders, especially in the presence of intellectual disability. Randomized controlled trials for each single neurodevelopmental disorder are now warranted to conclusively demonstrate the efficacy of these mitochondrial bioenergetic and antioxidant agents and to estimate their therapeutic effect size.